Diarrhoeal Disorders in the Philippines - Perla D. Santos-Ocampo; Alicia O. Caspellan; Ninofar Z. Porras; Maridel Borja; Carmelita Belmonte-Cuyugan; Celerino Bernas (Indonesian Pediatric Society, 1978)
Lactose malabsorption exists in almost half of Filipinos, however, diarrhea due to lactose malabsorption found in association with diarrheas is very commonly encountered. This paper mentions solutions to the problem of diarrheal disorders, including early and accurate diagnosis and management. Specific management stresses both oral and intravenous rehydration, dietary management, correction of protein-energy malnutrition and antibiotic therapy, as necessary.